2016
DOI: 10.3389/fpsyg.2016.01971
|View full text |Cite
|
Sign up to set email alerts
|

Monkeys Share the Human Ability to Internally Maintain a Temporal Rhythm

Abstract: Timing is a fundamental variable for behavior. However, the mechanisms allowing human and non-human primates to synchronize their actions with periodic events are not yet completely understood. Here we characterize the ability of rhesus monkeys and humans to perceive and maintain rhythms of different paces in the absence of sensory cues or motor actions. In our rhythm task subjects had to observe and then internally follow a visual stimulus that periodically changed its location along a circular perimeter. Cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 60 publications
(86 reference statements)
1
31
0
Order By: Relevance
“…Negative lag‐1 autocorrelations are typical in tapping sensorimotor STs in humans . Another study showed that macaques can internally follow a visual isochronous beat for a range from three to six intervals as accurately as human participants when a two‐choice response is presented to them . Therefore, monkeys are capable of isochronous beat entrainment when the proper training and feedback is given to them, highlighting the importance of the training strategy, the reward contingencies, and the performance feedback given to the animals, as discussed by Wilson and Cook .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Negative lag‐1 autocorrelations are typical in tapping sensorimotor STs in humans . Another study showed that macaques can internally follow a visual isochronous beat for a range from three to six intervals as accurately as human participants when a two‐choice response is presented to them . Therefore, monkeys are capable of isochronous beat entrainment when the proper training and feedback is given to them, highlighting the importance of the training strategy, the reward contingencies, and the performance feedback given to the animals, as discussed by Wilson and Cook .…”
Section: Discussionmentioning
confidence: 92%
“…1,23 Another study showed that macaques can internally follow a visual isochronous beat for a range from three to six intervals as accurately as human participants when a two-choice response is presented to them. 43 Therefore, monkeys are capable of isochronous beat entrainment when the proper training and feedback is given to them, highlighting the importance of the training strategy, the reward contingencies, and the performance feedback given to the animals, as discussed by Wilson and Cook. 20,21 An important conclusion, therefore, is that these constraints need to be taken into consideration when designing experimental paradigms with the aim to reveal deeper capacities of nonhuman primates and the evolutionary origins of beat perception and entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…The scalar property states that temporal variability increases linearly as a function of timed duration [35]. This hallmark feature of temporal processing has been documented across many timing tasks and species [9,[35][36][37][38]. Several computational models based on neural population time representations have been implemented to describe this property including drift diffusion [39,40] and recurrent networks [26,41].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is evident when we dance to music, which requires perceiving rhythms and generating movements in sync with them (Levitin, Grahn, and London 2018). Nonhuman primates and other vertebrates are capable synchronizing their movements to periodic rhythms (Merchant et al 2013; Takeya et al 2017), and we recently showed that monkeys can internally maintain rhythms of different tempos in the absence of overt motor actions (García-Garibay et al 2016). Ample evidence indicates that cortical and subcortical motor circuits participate in behavioral tasks that require time perception and temporally precise behavioral responses (Mita et al 2009; Crowe et al 2014; Bartolo, Prado, and Merchant 2014; Merchant and Averbeck 2017; Grahn and Brett 2007; Ivry 2004; Murray et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We developed a novel visual metronome task in which nonhuman primates had to observe, and then internally maintain, a temporal rhythm defined by a left-right alternating visual stimulus. Crucially, subjects performed had to track the rhythm in the absence of overt movements (García-Garibay et al 2016). By uncoupling rhythm encoding and maintenance from motor actions, we aimed to identify the mechanism that allows the brain to internally maintain rhythms of different tempos.…”
Section: Introductionmentioning
confidence: 99%